R WE ready for reimbursement? A round up of developments in real-world evidence relating to health technology assessment: part 14 - Benjamin D Bray; Sreeram V Ramagopalan (Becaris Publishing Limited, 2024)
In this latest update we highlight: a publication from the US FDA regarding the definitions of real-world data (RWD) and real-world evidence (RWE); a publication from academic researchers on a demonstration project for target trial emulation; a publication from the National Institute of Health and Care Excellence (NICE) on the 1 year anniversary of their RWE framework; and a publication from NICE and Flatiron Health on the utility of US RWD for initial UK health technology assessment decision making.